1994
DOI: 10.1017/s002211209400011x
|View full text |Cite
|
Sign up to set email alerts
|

Stretched vortices – the sinews of turbulence; large-Reynolds-number asymptotics

Abstract: A large-Reynolds-number asymptotic theory is presented for the problem of a vortex tube of finite circulation [Gcy ] subjected to uniform non-axisymmetric irrotational strain, and aligned along an axis of positive rate of strain. It is shown that at leading order the vorticity field is determined by a solvability condition at first-order in ε = 1/R[Gcy ] where R[gcy ] = [gcy ]/ν. The first-order problem is solved completely, and contours of constant rate of energy dissipation are obtained and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
243
0
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(268 citation statements)
references
References 15 publications
16
243
0
8
Order By: Relevance
“…In Section 2.1 it is shown that an unusual decoupling takes place between ω 3 and W with γ satisfying a nonlinear equation which is related to the second z-derivative of the pressure p zz which is constrained to be spatially uniform. The second stage is to solve these equations for ω 3 and W . To construct stretched vortex solutions of Burgers type it is necessary to be more specific with the velocity field in Eq.…”
Section: (X Y T) γ (X Y T)z + W (X Y T))mentioning
confidence: 99%
See 4 more Smart Citations
“…In Section 2.1 it is shown that an unusual decoupling takes place between ω 3 and W with γ satisfying a nonlinear equation which is related to the second z-derivative of the pressure p zz which is constrained to be spatially uniform. The second stage is to solve these equations for ω 3 and W . To construct stretched vortex solutions of Burgers type it is necessary to be more specific with the velocity field in Eq.…”
Section: (X Y T) γ (X Y T)z + W (X Y T))mentioning
confidence: 99%
“…(42) to which we turn in Section 3.2. Before this, however, we discuss axisymmetric solutions for 3 and W.…”
Section: Solutions Of the Navier-stokes Equationsmentioning
confidence: 99%
See 3 more Smart Citations